DISEÑO DE UN CIRCUITO TURÍSTICO PARA CONTRIBUIR AL DESARROLLO DEL TURISMO EN LOS ATRACTIVOS DEL CANTÓN QUEVEDO AÑO 2022. - Suarez Ruiz, Mildree Aidy (2022)
Tourism has become an important axis of economic development today, which is why each year greater investment budgets are allocated to promote the emblematic places of each country. The objective of the present investigation Design a tourist circuit to contribute to the development of tourism in the attractions of the Quevedo canton, the lack of a tourist circuit has influenced so that many places that are considered interesting go unnoticed because the tourist does not know about its location and activities that can be carried out in the area. For the development of this study, the analytical, deductive and inductive methods were applied, together with the types of research that describe and explain how the design of a tourist circuit will contribute to making the respective conclusions about the conditions and characteristics of the canton as a tourist potential. that have not been fully exploited, which is why it is appropriate that a financial and economic evaluation be included in the design of the tourist circuit to determine the amount of investment for its development, taking into account the environmental impact, promoting responsible tourism with the ecosystem and their communities.